Diseño de un sistema eléctrico alimentado con energía solar fotovoltaica para la empresa Gog Ingenieria Electrica Ltda de la ciudad de Cúcuta, Norte de Santander (2021)
The present degree work is oriented to the design of an electrical system powered by solar energy photovoltaic for the company GOG Ingeniería Eléctrica Ltda. of the city of Cúcuta, Norte de Santander. In order for the place to have an adequate electrical installation complying with current regulations and guaranteeing the safety and reliability necessary for the development of its activities. The design will carry out a study of the loads to establish the necessary power to install and carry out calculations to choose conductors, conduits and protections. Additionally, the photovoltaic system will be designed to allow this demand to be supplied with electricity. For the lighting system, the use of lamps was considered LEDs to replace the existing ones that will provide greater visual comfort for users as well as significant savings in electrical power consumption, therefore, in the choice of conductor gauge and pipe diameter.